TO THE CALCULATION OF A LINEAR STEPPER MOTOR WITH INCREASED TRACTION FORCE - KOSENKOV, VOLODYMYR; MARTYNYUK, VALERIY; POLISHCHUK, OLEH; LISEVYCH, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The design of a linear stepper electric motor, in which the traction force is determined by the normal component of magnetic induction in the working air gap, is considered, and the main relations for calculating such a motor in a cylindrical design are given. Linear stepper motors provide precise control and precise positioning for a wide range of applications. Their ability to convert electrical energy into linear motion determines their use in robots, automation, medical equipment, and consumer electronics. In practice, two fundamentally different approaches to obtaining linear motion are used. The first approach: a rotary-type stepper motor and a mechanical converter of angular motion into linear motion, for example, a rack-and-pinion transmission, are placed in one housing. The stepper motor usually has a multiphase winding on the stator and a permanent magnet on a ferromagnetic rotor (the so-called active version). To be able to adjust the movement step, a guide rod with a different pitch of saw-tooth grooves and a corresponding adjustment of the distance between the traction electromagnets was used. Mechanical contact between the moving and stationary parts of the motor, it is designed to operate in modes with infrequent switching on, for example, in the rotation system of a solar tracker. The second approach: the stationary part is a ferromagnetic base with ferromagnetic protrusions, which are located along the entire length of the movement. And the moving part contains control windings on ferromagnetic cores and a permanent magnet for fixing the position when the windings are turned off. That is, here we have a direct conversion of electromagnetic field energy into linear motion. This option is subject to improvement.